Language on the screen: the case of non-obvious obviousness in translation - Deckert, Mikołaj (Język(i) w czasie i przestrzeni, 2021)
The paper deals with language on the screen in a twofold sense. First, the focus is literally on language that is represented in its visual form, as text that the receptor retrieves from the screen. Second, in a broader sense, we are dealing with language “on the screen” coded more prototypically, i.e. aurally, as utterances in the audiovisual product. The paper’s point of departure is to isolate two general phases in the process of translatorial decision making. The first phase consists in identifying the problem which is the subject of decision making. In the second phase a decision is made with respect to that problem. This generalised formula makes it possible to explore the hypothesis that in interlingual translation – in our particular case additionally of multimodal character – the task of selecting the target variant can be relatively easy when viewed against the challenge of realising that there is an element to potentially be decided upon.